The implementation of sima’an Al-Qur’an activities to improve memorization quality - Wahyudin (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Memorizing the Qur'an requires continuous support and strategic activities to enhance memorization quality. Sima’an al-Qur’an, a traditional recitation program, plays a vital role in reinforcing students’ (santri’s) hafalan (memorization). This study investigates how this activity is planned and executed, as well as the supporting and hindering factors in its implementation at Tahfidzul Qur'an Islamic Boarding School (PPTQ) Al-Amin Aminullah Barandasi. Methods: This qualitative study was conducted at PPTQ Al-Amin Aminullah Barandasi. Data were collected through observation, interviews, and documentation. The participants included the pesantren’s leaders, mentors, and sima’an participants. The instruments used were interview guidelines, observation sheets, and documentation templates. Findings: The planning of the sima’an al-Qur’an activity is carried out systematically in three stages: surveying the venue and time, determining participants and readings, and preparing necessary facilities. The implementation follows a structured format with sessions for opening, recitation, breaks, and closing. Supporting factors include the commitment of organizers and participants, institutional support, and adequate facilities. In contrast, barriers include limited space, insufficient preparation, and interruptions from other activities. Conclusion: Sima’an al-Qur’an is effectively planned and implemented at PPTQ Al-Amin Aminullah Barandasi and contributes significantly to improving santri’s memorization quality. The pesantren is encouraged to further optimize and expand the program to benefit more students. Novelty/Originality of this article: This study provides a detailed, practice-based account of how sima’an al-Qur’an activities enhance Qur’anic memorization in Islamic boarding schools. Its originality lies in highlighting both practical implementation and institutional strategies, offering a replicable model for other pesantren.